Applicability of a Monoclonal Antibody-Based Stool Antigen Test to Evaluate the Results of Helicobacter pylori Eradication Therapy - Kato, Chieko; Fukuda, Yoshihiro; Kodama, Masaaki; Kobayashi, Intetsu; Shimoyama, Tadashi (Japanese Journal of Infectious Diseases, 2009)
The 13C-urea breath test (UBT) is widely used to examine the results of eradication therapy for Helicobacter pylori. We examined whether a stool antigen test can be used as efficiently as UBT. (i) Ninety-four patients infected with H. pylori underwent eradication therapy. Six or eight weeks after the completion of treatment, the results were evaluated by UBT and a stool antigen test (TPAg). In 77 out of 78 patients who had negative UBT results, the TPAg results were also negative. Among the 16 UBT-positive patients, 12 were also positive by TPAg. Agreement of UBT and TPAg was 94.7%. (ii) Twenty-two patients with peptic ulcers in the active stage also received eradication therapy followed by proton pump inhibitor (PPI) administration. TPAg and UBT were performed to examine the results of eradication therapy at the end of PPI administration and at least 7 days after its discontinuation. Of the 22 patients taking PPIs, TPAg evaluated the results of eradication therapy accurately in 21 patients. TPAg appears to be an accurate test for evaluating the results of H. pylori eradication therapy, and to be as efficient as 13C-UBT. Use of the stool antigen test should be considered as an alternative, particularly in patients who have to take PPIs in order to avoid the risk of peptic ulcers.